2021
DOI: 10.5500/wjt.v11.i11.480
|View full text |Cite
|
Sign up to set email alerts
|

Native and transplant kidney histopathological manifestations in association with COVID-19 infection: A systematic review

Abstract: BACKGROUND Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can result in clinically significant multi-system disease including involvement in the kidney. The underlying histopathological processes were unknown at the start of the pandemic. As case reports and series have been published describing the underlying renal histopathology from kidney biopsies, we have started to gain an insight into the renal manifestations of this novel disease. AIM To provide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…During the last year, CG has been defined as the most frequent histopathological diagnosis for COVID-19 patients with acute renal failure or proteinuria [1], giving birth to the term COVID-19 associated nephropathy (COVAN). It has also been described in kidney grafts [2,3,15]. One of the possible mechanisms for this kidney damage is the direct toxicity of the virus since autopsy studies have shown its presence in the kidneys [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last year, CG has been defined as the most frequent histopathological diagnosis for COVID-19 patients with acute renal failure or proteinuria [1], giving birth to the term COVID-19 associated nephropathy (COVAN). It has also been described in kidney grafts [2,3,15]. One of the possible mechanisms for this kidney damage is the direct toxicity of the virus since autopsy studies have shown its presence in the kidneys [16].…”
Section: Discussionmentioning
confidence: 99%
“…Both de novo glomerulonephritis and relapses have been reported. Among them, focal segmental glomerulosclerosis (FSGS) has been highlighted, specifically the collapsing glomerulonephritis (CG) variant [1][2][3]. Likewise, administration of the vaccine to the population has revealed cases of glomerulonephritis.…”
Section: Introductionmentioning
confidence: 99%
“…CG has previously been reported to associate with multiple infections and inflammatory conditions, namely HIV and systemic lupus erythematous [ 43 ]. Previous reviews evaluating COVID-19 induced glomerular disease in adults suggest CG to be amongst the most prevalent histopathological presentations [ 3 , 44 ]. The pathogenesis of CG is currently believed to be a multifactorial process associated with both direct viral invasion of glomerular structures and cytokine release [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus disease (COVID-19) that began in 2019 has spiraled into a global pandemic, continuing up to this day, since the identification of the first severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) case in Wuhan, China, in December 2019 [ 1 , 2 ]. Whilst data relating to the epidemiology, pathophysiology, risk factors and prognosis of adults with kidney histopathology following acute COVID-19 infection are becoming more well-established, there remains a sizable knowledge gap in our understanding of intrinsic pathological kidney manifestations in children following acute COVID-19 infection [ 3 ]. This is likely explained by the fact that children and adolescents only form about 1–2% of all COVID-19 cases reported globally [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors observing KTx patients affected by COVID-19 infections [20][21][22][23][24][25][26][27][28][29][30] have described different aspects. The authors are still debating whether the lesions are to be ascribed directly to the virus or if the virus acts indirectly.…”
Section: Renal Histopathologymentioning
confidence: 99%